Post Operative Diagnosis of Early Gastric Cancer in a Low Risk Population and the Possibility of Risk Stratified Screening - Ghimire, B; Singh, YP; Timalsina, S (Kathmandu University Medical Journal, 2015)
Background Gastric cancer is the second commonest cause of cancer related mortality worldwide. Though its incidence is more in Eastern Asia, it is increasing in the South Asian subcontinent. The diagnosis of early gastric cancer (EGC) confined to the mucosa or submucosa, is an important concern due to a better outcome at this stage where five year survival rates could increase by 90 percent. Though mass screening is done in few countries, it has not been applied in developing countries like Nepal. Preoperative diagnosis of EGC is rare in Nepal. The aim of this study is to analyze the clinico-pathological features of postoperative cases of gastric cancer managed in a tertiary care university hospital of Nepal.Methods All patients with histological diagnosis of gastric cancer admitted in the Department of Surgery, Tribhuvan University Teaching Hospital, Kathmandu, Nepal during the three year period (September 2010 to August 2013) were analyzed retrospectively.Results Ninety two patients with endoscopic diagnosis of gastric cancers were admitted during the past three years. The mean age was 60 years ranging from 28 years to 85 years with the male to female ratio of 2.8:1. Five patients were younger than 40 years and all were in advanced stage. Thirty five percent of the patients belonged to Janajatis (Hill) community though they comprise only 23% of the population and about 65% of them belonged to an area involving 25% of the country.Seventy six cases were operated. Out of 92 patients, 4 patients were diagnosed as early gastric cancer postoperatively. All patients with early gastric cancer were above 50 years with CT Scan abdomen revealing focal thickening without lymphadenopathy.Conclusion Over the years, the incidence of gastric cancer is increasing in Nepal. Though 92% are advance gastric cancers, few have been diagnosed and treated early. A screening program in a country like Nepal with diverse ethnicity and difficult terrain might be helpful if it targets high risk people in high risk areas.Kathmandu University Medical Journal Vol.12(1) 2014: 32-37